Resenhas - Morelato, Adrienne Kátia Savazoni; Guerini, Andréia; Knorr, Eliane; Borges, Joana Vieira; Gallina, Justina Franchi; Vavassori, Mariana Barreto; Miskolci, Richard; Muller, Rita Cássia Flores; Sacramento, Sandra (Revista Estudos Feministas, 2006)
Resenhas